IV International Conference on mental health care “Mental Health: Global challenges of XXI century” - Skurat, Katia (Psychosomatic Medicine and General Practice, 2020)
IV International Conference on mental health care “Mental Health: Global challenges of XXI century” 12-14th November 2020